2006
DOI: 10.1021/jp0632236
|View full text |Cite
|
Sign up to set email alerts
|

DFT/TDDFT Study of LanthanideIII Mono- and Bisporphyrin Complexes

Abstract: Electronic structure, molecular structure, and electronic spectra of lanthanide III mono-and bisporphyrin complexes are investigated using a DFT/TDDFT method. These complexes include YbP (acac), YbP 2 , [YbP 2 ] + , YbHP 2 , and [YbP 2 ] − (where P = porphine and acac = acetylacetonate). To shed some light on the origin of the out-of-plane displacement of Yb in YbP(acac), unligated model systems, namely planar D 4h and distorted C 4v YbP, were calculated. For comparison, the calculations were also extended to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 47 publications
(121 reference statements)
3
13
0
Order By: Relevance
“…This study showed that different ligand C-H vibrations contribute to the quenching of the Er III luminescence, the calculated emission lifetime being in good agreement with the experimental value [249]. Finally, TDDFT calculations including the 4f electrons in the valence space were successfully used to calculate the absorption spectra Ln III mono-and bisporphyrin complexes [250], and Lu III bisphthalocyanines [251].…”
Section: Methodssupporting
confidence: 69%
“…This study showed that different ligand C-H vibrations contribute to the quenching of the Er III luminescence, the calculated emission lifetime being in good agreement with the experimental value [249]. Finally, TDDFT calculations including the 4f electrons in the valence space were successfully used to calculate the absorption spectra Ln III mono-and bisporphyrin complexes [250], and Lu III bisphthalocyanines [251].…”
Section: Methodssupporting
confidence: 69%
“…Previous calculations of the energy levels of double-decker complexes have shown poor agreement with experiments 47,48 . Herein, the absorption spectrum was modeled from the optimized structure by two programs.…”
Section: Resultsmentioning
confidence: 86%
“…The quantum chemical methods provide an effective way to investigate these reactions at molecular level. With density functional theory (DFT) and time-dependent density functional theory (TD-DFT), Liao et al [35] successfully predicted the molecular structures of lanthanide mono-and bisporphyrin complexes. Yin [36] calculated the free energies of deprotonated and protonated species of prophyrin, and showed which process was thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%